2020
DOI: 10.1038/s41419-020-02750-0
|View full text |Cite
|
Sign up to set email alerts
|

ω-6 Polyunsaturated fatty acids (linoleic acid) activate both autophagy and antioxidation in a synergistic feedback loop via TOR-dependent and TOR-independent signaling pathways

Abstract: ω-6 Polyunsaturated fatty acids (PUFAs) are essential fatty acids that participate in macroautophagy (hereafter referred to as autophagy) and the Kelch ECH-associating protein 1 (Keap1)—nuclear factor erythroid 2-related factor 2 (Nrf2) antioxidant system in organisms. However, the molecular mechanisms by which ω-6 PUFAs (linoleic acid) regulate autophagy and Keap1–Nrf2 antioxidant system are not completely understood. Therefore, the purposes of this study were to explore the molecular mechanisms by which ω-6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 40 publications
2
40
0
Order By: Relevance
“…In mammalian cells, α-linoleic acid is converted to conjugated ω-3 isomers (DHA, EPA, and docosapentaenoic acid-DPA-22:5n), while linoleic acid via γ-linolenic acid is metabolized to arachidonic acid and eicosadienoic acid (20:2n-6) through the other pathway [77]. DHA and EPA can activate the Keap1/Nrf2 signaling pathway, the major route triggering antioxidant cell response, via stimulation of Nrf2 transcription factor [78,79]. An oxidized metabolite of linoleic acid (12,13-epoxy-9-keto-10(trans)-octadecenoic acid (EKODE)) initiated antioxidant response in neuroblastoma cells and cerebrocortical neurons via activation of the antioxidant response element (ARE), the expression of which is governed by the Nrf2 transcription factor [78].…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian cells, α-linoleic acid is converted to conjugated ω-3 isomers (DHA, EPA, and docosapentaenoic acid-DPA-22:5n), while linoleic acid via γ-linolenic acid is metabolized to arachidonic acid and eicosadienoic acid (20:2n-6) through the other pathway [77]. DHA and EPA can activate the Keap1/Nrf2 signaling pathway, the major route triggering antioxidant cell response, via stimulation of Nrf2 transcription factor [78,79]. An oxidized metabolite of linoleic acid (12,13-epoxy-9-keto-10(trans)-octadecenoic acid (EKODE)) initiated antioxidant response in neuroblastoma cells and cerebrocortical neurons via activation of the antioxidant response element (ARE), the expression of which is governed by the Nrf2 transcription factor [78].…”
Section: Discussionmentioning
confidence: 99%
“…Large yellow croaker ( Larimichthys crocea ) is an economic important marine fish species in south China ( 18 ). Similarly to most marine fish species, large yellow croaker larvae had an undifferentiated and undeveloped gut and accessory organs ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the family, major chemical compositions 63 , parts that were used and their applications in TPM 64 were reviewed in Supplementary Table S4 online. Review of modern academic literature confirmed that these herbs contain many compounds (63 out of 1078) that may exert anti-aging effects by inducting autophagy process, through targeting several signaling pathways 65 131 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the highest percentage of fatty acid in Juglans regia L. corresponds to linoleic acid, oleic acid, and palmitic acid. The effects of these phytochemicals in inducing autophagy were documented by different research groups 84 , 96 , 131 , 135 .…”
Section: Resultsmentioning
confidence: 99%